Simple Preparations and Characterizations of Activated-Carbon- Clothes from Palm-Kernel-Shell for Ammonia Vapor Adsorption and Skim-Latex-Odor Removal - Muhammad Adlim; Ratu Fazlia Inda Rahmayani; Fitri Zarlaida; Latifah Hanum; Maily Rizki; Nurul Ummi Manatillah; Omar Muktaridha (Universitas Gadjah Mada, 2021)
This study explored a simple preparation and characterization of the activated carbon and cloth from the palm kernel shell and compared it to the commercial-water-filter-carbon specification. A new pyrolysis chamber that is easily scaled up using the palm kernel shell itself as a heat source was tested. Two different steps were compared: the alkaline activation process performed before or after the carbonation process in the palm-kernel-shell carbon preparation. The palm-kernel-shell activated carbons prepared with the current method fulfilled the standard quality of activated charcoal except for the ash content. The sequencing step of the preparation affected the adsorption capacity. Instead of the reverse sequence, the soaking palm kernel shells in NaOH before the carbonation process lead to a higher adsorption capacity. The carbon particle stability on the cloth surface was affected by both the adhesive concentration and its size. The ammonia adsorption capacity of activated carbon cloth (ACC) was between 1–4 mg ammonia per g stuck carbon. The preparation and the carbon type source on ACC affected the adsorption capacity. The ACC absorbed and lessened the skim latex odor vapor, nearly odorless depending on the ACC area and the volume of odor vapor.